ANALISIS PUTUSAN PENGADILAN NEGERI GORONTALO NOMOR 209/PID.SUS/2021 BERKAITAN DENGAN TINDAK PIDANA NARKOTIKA YANG DILAKUKAN DENGAN PEMUFAKATAN JAHAT - TAHIR, RACHMAD (Fakultas Hukum Universitas Muhammadiyah Palu, 2024)
The results of the research show that the Gorontalo City Consumer Dispute Resolution Agency in the last 3 years has data in 2021 that has resolved 3 cases, in this case 2 mediations and 1 arbitration. Furthermore, in 2022 there will be 17 cases with the qualification of 15 mediation cases and 2 of them are cases carried out by arbitration. As of the latest data, which is currently running in 2023, the Gorontalo City Consumer Dispute Resolution Agency has resolved 14 mediation cases and 2 arbitration cases. In Consumer Dispute Resolution, it is carried out using the trial principle which produces decisions quickly, simply and without costs, but in fact there are still decisions which charge court costs to the parties, namely cases number 003 and 004 in 2021 and 2022. For this reason, 2 (two) Aquo's decision is part of an evaluation of the Gorontalo City Consumer Dispute Resolution Agency to include legal considerations in a case that is subject to and complies with the Consumer Protection Law.